2022
DOI: 10.1007/s00540-022-03048-5
|View full text |Cite
|
Sign up to set email alerts
|

Paths of thoracic epidural catheters in children undergoing the Nuss procedure for pectus excavatum repair

Abstract: Purpose To investigate the paths of thoracic epidural catheters in children, this retrospective study was performed. Methods We investigated 73 children aged 4 to 12 (mean ± SD 7.8 ± 2.3) years, who underwent the Nuss procedure for pectus excavatum repair under combined general and epidural anesthesia over a 5-year period at Tokyo Metropolitan Police Hospital. Following induction of general anesthesia, we inserted a radiopaque epidural catheter via the T5/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This may be because the residents were more likely to insert the epidural needle near the left side of the patient, and so the nerve roots on the left side of the epidural space were more likely to be irritated and cause paresthesia when the catheter was inserted. The catheters used in our study were stiff, which may have induced greater incidence of paresthesia and intravascular cannulation than wire-embedded catheters [ 6 8 ]. A previous study reported that the angle formed between the patient’s back skin and the needle in the coronal plane was greater than 90° in groups U and R [ 3 ]; this might increase the risk of the spinal needle being inserted closer to the right side compared with the epidural needle.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the residents were more likely to insert the epidural needle near the left side of the patient, and so the nerve roots on the left side of the epidural space were more likely to be irritated and cause paresthesia when the catheter was inserted. The catheters used in our study were stiff, which may have induced greater incidence of paresthesia and intravascular cannulation than wire-embedded catheters [ 6 8 ]. A previous study reported that the angle formed between the patient’s back skin and the needle in the coronal plane was greater than 90° in groups U and R [ 3 ]; this might increase the risk of the spinal needle being inserted closer to the right side compared with the epidural needle.…”
Section: Discussionmentioning
confidence: 99%